Defence cooperation between Brazil and Namibia: Enduring ties across the South Atlantic - Seabra, Pedro (2016)
This article addresses the nature of transatlantic relations between Brazil and Namibia in the last two decades and argues that, in stark contrast with any other relationship regarding the African continent, Brazil's motivation in deepening ties with Namibia was largely built upon an extensive military-to-military cooperation partnership. By focusing on long-standing bureaucratic interests, the article demonstrates how Brazilian–Namibian relations were driven over the years by strategic affinities, business opportunities made available by the security sectors of both countries and, more recently, growing concerns over the sovereignty of their respective maritime areas in tandem with renewed interest for security developments within the the South Atlantic region.